“Sistema de gestión de historias clínicas y citas médicas para el departamento médico de la Universidad Técnica De Cotopaxi Extensión La Maná.” - Gonzáles Espinales, Josselin Katherine (2022)
This research project focuses on the development of a management system for clinical records and medical appointments for the medical department of the Technical University of Cotopaxi Extension La Maná, where the processes or procedures currently carried out by the medical area are by means posters or physical and printed forms that the patient has to register to receive care, in such a way to control and record information to convert it into clinical history. In order to know the procedures carried out by the person in charge of the medical department, the type of field research was applied to describe its aspects and functionality; also with the applications of techniques such as the interview that allowed us to expand knowledge and establish the requirements for the development of the system, where the surveys carried out provided the first fruits to demonstrate the need for the creation of the application. Therefore, it was possible to identify the development tools through the PHP programming language and the database engine necessary for this program is MySQL, together with the Scrum methodology, it was made that the web system can access with username and password, where The dashboard will be displayed where all the activities of registering patients, appointments and the necessary consultations of the clinical history will be, allowing a printed copy of the patient's information to be extracted. Where the system responds to the needs of the digital transformation of the manual processes of the institution's medical department.